Penguatan Kesadaran Masyarakat tentang Risiko Penyakit Malaria pada Musim Hujan - Asrori Abdul Aziz (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase public awareness of the risk of malaria during the rainy season. The rainy season increases the amount of stagnant water that becomes a breeding ground for Anopheles mosquitoes, the main vector that causes malaria. Through an educational approach, this activity educates the public about the importance of prevention, early detection, and control of malaria mosquitoes, especially during the rainy season. This activity was carried out in Sugian Hamlet, Sugian Village, Sambelia District, East Lombok Regency by involving various levels of society, including religious leaders, the general public, and health workers. The results of this activity are to strengthen public understanding of ways to prevent malaria and increase their participation in malaria control efforts in the surrounding environment.